A descriptive epidemiological study on the patterns of occupational injuries in a coastal area and a mountain area in Southern China. Issue 3 (18th June 2012) - Li, Liping; Liu, Xiaojian; Choi, Bernard C K; Lu, Yaogui; Yu, Min
Abstract : Objectives: This study compared patterns of occupational injuries in two different areas, coastal (industrial) and mountain (agricultural), in Southern China to provide information for development of occupational injury prevention measures in China. Design: Descriptive epidemiological study. Setting: Data were obtained from the Hospital Injury Surveillance System based on hospital data collected from 1 April 2006 to 31 March 2008. Participants: Cases of occupational injury, defined as injury that occurred when the activity indicated was work. Outcome measures: Distribution and differences of patterns of occupational injuries between the two areas. Results: Men were more likely than women to experience occupational injuries, and there was no difference in the two areas (p=0.112). In the coastal area, occupational injury occurred more in the 21–30-year age group, but in the mountain area, it was the 41–50-year age group (p<0.001). Occupational injuries in the two areas differed by location of hometown, education and occupation (all p<0.001). Occupational injuries peaked differently in the month of the year in the two areas (p<0.001). Industrial and construction areas were the most frequent locations where occupational injuries occurred (p<0.001). Most occupational injuries were unintentional and not serious, and patients could go home after treatment. The two areas also differed in external causes and consequences of occupational injuries. Conclusions: The differing patterns of occupational injuries in the coastal and mountain areas in Southern China suggest that different preventive measures should be developed. Results are relevant to other developing countries that have industrial and agricultural areas.